Penggunaan Model Pimca dalam Pembelajaran Fisika Materi Pembiasan Cahaya Dengan Graphline - Indah Ula; Cosmas Poluakan; Farly Reynol Tumimomor (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Research was carried out on physics learning models using light refraction material with graph line. The purpose of this study is to determine student learning outcomes using the PIMCA (Presentation, Idea Mapping, Conceptualization and Formative Assessment) model introduced and developed by Cosmas Poluakan. This study was carried out at SMA Negeri 1 Passi with a number of participants of up to 20 students. The design of this study is based on the One Group Pretest-Posttest-Design. The instruments used in this study were pretest and posttest. The process of this research starts with the pretest, implementing physics learning by following the 4 steps of the PIMCA model, and ends with the posttest. The results of the descriptive statistics showed an average pretest score of 30.00 and a posttest score of 77.77 with a difference of 47.77. From the results of the analysis with the N-Gain test, there were 10 students who experienced an increase in learning outcomes in the high category, 9 students who experienced an increase in learning outcomes in the middle category, and 1 student who experienced an increase in the Learning outcomes in the lower category. With a percentage of 50% of students experiencing an increase in learning outcomes in the high category. Thus, the results of this study show that the PIMCA learning model is very effective in learning physics.